1995
DOI: 10.1063/1.114544
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition of diamond from graphite targets

Abstract: Diamond crystals of 1 μm mean size were grown on (100) silicon substrates by ArF (193 nm) laser ablation of graphite in a hydrogen atmosphere with a laser power density of 1.3×108 W/cm2 at relatively low substrate temperature (450 °C). Raman spectroscopy analysis confirmed the diamond cubic structure of the crystals by the presence of a sharp peak at 1332 cm−1. When a KrF (248 nm) laser was used instead of the ArF no diamond phases were detected in the deposited films and the Raman spectra showed only the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Particularly, the deposition of amorphous carbon films with diamond-like characters has been widely reported by laser ablation of graphite in vacuum [214][215][216][217][218][219][220][221][222][223][224][225][226][227], in which some researchers reported the growth of crystalline particles, but the lack of a diamond peak in Raman spectra was a common result in all reports. It was not until in 1995 that Polo and co-workers [228] first showed the Raman spectroscopy analysis of the sample that is confirmed to have diamond cubic structure of the crystals by the presence of a sharp peak at 1332 cm À1 . In 1992, Ogale and co-workers [19] first reported that diamond particulates with cubic structure were detected from the production of pulsed ruby laser irradiation of the pyrolytic graphite target in the benzene solution.…”
Section: Diamond Nanocrystalsmentioning
confidence: 91%
“…Particularly, the deposition of amorphous carbon films with diamond-like characters has been widely reported by laser ablation of graphite in vacuum [214][215][216][217][218][219][220][221][222][223][224][225][226][227], in which some researchers reported the growth of crystalline particles, but the lack of a diamond peak in Raman spectra was a common result in all reports. It was not until in 1995 that Polo and co-workers [228] first showed the Raman spectroscopy analysis of the sample that is confirmed to have diamond cubic structure of the crystals by the presence of a sharp peak at 1332 cm À1 . In 1992, Ogale and co-workers [19] first reported that diamond particulates with cubic structure were detected from the production of pulsed ruby laser irradiation of the pyrolytic graphite target in the benzene solution.…”
Section: Diamond Nanocrystalsmentioning
confidence: 91%
“…I I O of these precursors, which often consists in small individual grains, allows to know if the processing conditions are correct or should be changed [37][38]. For example, the Raman spectrum of a single micro-crystal of figure 6(a) corresponds to that of a high quality diamond crystal whereas the spectrum of the thin film, shown in figure 6(b), indicates in addition of sp 3 carbons some degree of disorder and graphitic structures.…”
Section: Thickness (Nm)mentioning
confidence: 99%
“…The film growth rate can be controlled by changing the UV laser pulse frequency. Some attempts to grow diamond by pulsed laser deposition using graphite targets in a hydrogen atmosphere have been reported 16,17 . Here we examined the possibility of hydrogen-free growth of diamond films on sapphire substrates by the pulsed laser deposition process using a graphite target under a partial pressure of oxygen.…”
Section: )mentioning
confidence: 99%